SOSIALISASI PENYAKIT ZOONOSIS ESCHERICHIA COLI O157:H7 SERTA PELAYANAN KESEHATAN SAPI DI DUSUN LAMPU DESA CATUR KINTAMANI BANGLI - Suardana, I W.; Swacita, I.B.N.; Suartha, I.N.; Sudisma, I G.N.; Rudyanto, M.D.; Krisna Erawan, I.G.M.; Suarsana, I.N.; Batan, I.W.; Sisyawati Putriningsih, P.A.; Sari Nindia, T.; Rompis, A.L.T.; Mantik Astawa, I.N.; et al. (Buletin Udayana Mengabdi, 2017)
Cattle suffering from diarrhea has great opportunity to reveal any zoonotic agent of E. coli O157:H7, according to cattle as the main reservoir of those agent. The transmission of bacterial strains to humans occurs mainly through consumption of meat with less cooked, unpasteurized dairy products, water contaminated with feces. Lampu sub-village as one of the area in the Catur village are known potentially for developing of livestock especially cattle. Its condition contribute to success of this program. The results of community service activities with theme “socialization of zoonotic disease E. coli O157:H7 and health care of cattle in this village, showed a positive response which is characterized by fairly large number of livestock which receive services as many as 65 cattles originated from 35 livestock farmers. The type of services performed including: spraying or giving butox of all cattle is 65 heads (100%), followed by administration of vitamin on 52 heads (80%),